Factors impeding African immigrant entrepreneurs' progression in selected small and medium enterprises: Evidence from a local municipality in South Africa - Bernard L. Ngota; Eric E. Mang'unyi; Sookdhev Rajkaran (South African Journal of Business Management, 2018)
This study examines factors inhibiting African immigrant entrepreneurs' small and medium enterprises' (SMEs) growth in a municipality of South Africa. Understanding these factors is important to stakeholders as this is an area that plagues much of the immigrant entrepreneurship literature. The study is descriptive in nature, and data were sourced from active African immigrant entrepreneurs through a quantitative approach. Random sampling was used to identify a total of 75 businesses. The results indicated that access to credit from regulated financial institutions is a mirage and that Afrophobic attacks on businesses dwindles prospects of entrepreneurship, job and wealth creation, thus impacting on economic growth of the region. To help bring `long-lasting' co-existence between immigrant entrepreneurs and natives, formulation and implementation of `liberal' integrated public policy interventions and strategies are needed. This would help in having a positive impact on the region's prosperity in terms of job creation, poverty reduction and economic growth, in turn improving the peoples' well-being. Given the migratory patterns and greater human global mobility, debate on integrated approaches among or within government systems should never be obscure as it is one of the biggest challenges in the continent.
Keywords: 650